PECULIARITIES OF USING INTERACTIVE TEACHING METHODS IN READING LESSONS - Pic, I.I. (Pedagogy of Higher and Secondary Education, 2010)
The article reveals the essence of the concept of interactive technology, their main provisions, described the benefits of using interactive teaching methods with traditional. Also analyzed various types of interactive teaching methods and provides guidelines for their use in the classroom of the Ukrainian reading in modern elementary school.